Modification effects of low-energy (∼10 eV/amu) carbon ion beams on naked DNA - P. Thopan (2019)
© 2019 Elsevier B.V. We have carried out a series of experiments on the ultra-low-energy ion beam bombardment of naked DNA to study the final stages of interaction between energetic ions and biological molecules and atoms. A carbon ion beam (carbon is the ion species usually used for cancer therapy) was used to bombard naked plasmid DNA pGFP to fluences of 1 × 1015, 2 × 1015 and 4 × 1015 ions/cm2 at the ultra-low energy of 50, 100 and 300 eV, or ∼10 eV/amu. Modification of the DNA in terms of topological form changes was investigated using gel electrophoresis. We find that there is a threshold of ion beam conditions for occurrence of the linear form indicating DNA double strand breakage (DSB), which is the dominant course for cell mutation or lethality. DNA DSBs can be brought about by carbon ion bombardment at the lowest ion energy of 50 eV and fluence of 4 × 1015 ions/cm2, or at the higher energy of 100 or 300 eV and the lowest fluence of 1 × 1015 ions/cm2. We discuss the origin of these threshold conditions using a simplified DNA double strand model as well as in terms of the chemical activity of carbon.